The Transcription Factor Zfx Regulates Peripheral T Cell Self-Renewal and Proliferation - Smith-Raska, Matthew R.; Arenzana, Teresita L.; D’Cruz, Louise M.; Khodadadi-Jamayran, Alireza; Tsirigos, Aristotelis; Goldrath, Ananda W.; Reizis, Boris (Frontiers in Immunology, 2018)
Peripheral T lymphocytes share many functional properties with hematopoietic stem cells (HSCs), including long-term maintenance, quiescence, and latent proliferative potential. In addition, peripheral T cells retain the capacity for further differentiation into a variety of subsets, much like HSCs. While the similarities between T cells and HSC has long been hypothesized, the potential common genetic regulation of HSCs and T cells has not been widely explored. We have studied the T cell-intrinsic role of Zfx, a transcription factor specifically required for HSC maintenance. We report that T cell-specific deletion of Zfx caused age-dependent depletion of naïve peripheral T cells. Zfx-deficient T cells also failed to undergo homeostatic proliferation in a lymphopenic environment, and showed impaired antigen-specific expansion and memory response. In addition, the invariant natural killer T cell (iNKT) cell compartment was severely reduced. RNA-Seq analysis revealed that the most dysregulated genes in Zfx-deficient T cells were similar to those observed in Zfx-deficient HSC and B cells. These studies identify Zfx as an important regulator of peripheral T cell maintenance and expansion, and highlight the common molecular basis of HSC and lymphocyte homeostasis.